Oroal manifestations in patients with multiple sclerosis - Grajales González Hilda María; Munive Báez Leticia (Instituto Nacional de Pediatría, 2014)
Multiple sclerosis is a chronic autoimmune inflammatory disease of the central nervous system, characterized by the presence of acute focal inflammatory demyelination, axonal loss and gliosis. It affects predominantly in young adults between 20 and 40 years of age; it is infrequent in the pediatric age. A observational, retrospective and descriptive cohort research was conducted between May 1999 and January 2012 to assess demographic characteristics, and pathological manifestations in the oral cav- ity of children with this condition. Records of 17 patients, under 18 years of age, of either sex were included, who had been evaluated in the Department of Stomatology. Data recorded were age, sex, State of origin, oral and facial pathological features, focal cavity infections and ceod index. There were no patients with trigeminal neuralgia or facial paralysis; a 5.7% ceod index was identified. Most of the patients were under immunopressive treatment. A protocol for stomatological follow-up in patients with multiple sclerosis does not exist. The medical profession must be sensibilized to establish strategies for an integral follow-up in patients with this condition.